Elimination of voltage and frequency deviations, suppression of chaotic oscillations in power system with distributed generation - B. A. Kosarev; V. K. Fedorov (Омский научный вестник)
The article proposes an algorithm for eliminating voltage and frequency deviations, suppressing chaotic oscillations in a power system with distributed generation. The operation of the algorithm by modeling in a SymPowerSystems (MatLab) software package is shown. Chaotic and pre-chaotic modes of operation are detected by the algorithm in the same way. If it is impossible to suppress the prechaotic and chaotic regimes of the same type of control action, it is proposed to supplement the algorithm with the calculation and evaluation of stability indicators. Existing algorithms for detecting and suppressing chaos do not take into account the requirements for indicators of the quality of electric energy; for their implementation, expensive measuring equipment is required. Therefore, the aim of the work is to develop an algorithm for detecting and suppressing chaotic oscillations in a power system with distributed generation taking into account the requirements for the quality indicators of electric energy and implemented by simple circuitry solutions.